Effect of water surface condition on survival, growth and swim bladder inflation of yellowfin tuna, Thunnus albacares (Temminck and Schlegel), larvae. (6th November 2014) - Honryo, Tomoki; Tanaka, Teruyoshi; Guillen, Angel; Wexler, Jeanne B; Cano, Amado; Margulies, Daniel; Scholey, Vernon P; Stein, Maria S; Sawada, Yoshifumi
Abstract: Early‐stage mortality due to surface water tension‐related death and due to sinking to the tank bottom was investigated for yellowfin tuna, Thunnus albacares (YFT), larvae. Different aeration rates and rearing water surface conditions were examined to evaluate the effect on larval survival, swim bladder inflation and growth. The percentage survival of yolk sac larvae was significantly higher when the rearing water surface was covered with fish oil at aeration rates of 0 and 50 mL min −1 . The highest mortality occurred at the highest aeration rate of 250 mL min −1 regardless of surface water condition. A second experiment was conducted twice under different water surface conditions: the water surface was covered by fish oil (FO), skimmed of fish oil (SS), and was not treated (NC). The percentage survival was not significantly different between treatments after 7 days of feeding. In contrast to the survival, the proportion of larvae with inflated swim bladders was significantly higher for the NC and SS groups than that of the FO group. Results of these experiments indicate that the addition of oil to the rearing water surface without its removal interferes with the initial swim bladder inflation in YFT larvae. These results also indicate that YFT larvae need to obtain (gulp) air at the water surface for initial swim bladder inflation, and success of initial swim bladder inflation may be crucial for their survival.